2018
DOI: 10.1016/j.physa.2018.04.104
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of sentence length measures in written texts

Abstract: Hidden structural patterns in written texts have been subject of considerable research in the last decades. In particular, mapping a text into a time series of sentence lengths is a natural way to investigate text structure. Typically, sentence length have been quantified by using measures based on the number of words and the number of characters, but other variations are possible. To quantify the robustness of different sentence length measures, we analyzed a database containing about five hundred books in En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Words were selected as a unit of measure for sentence length primarily because of the simplicity and the great prevalence of this approach. It is necessary to note that according to [37], sentence length is robust with respect to the selection of the unit of measurement. Thus, the choice of the word (and, e.g., not letters) will not lead to a change in the results of further analysis.…”
Section: Data For Analysismentioning
confidence: 99%
“…Words were selected as a unit of measure for sentence length primarily because of the simplicity and the great prevalence of this approach. It is necessary to note that according to [37], sentence length is robust with respect to the selection of the unit of measurement. Thus, the choice of the word (and, e.g., not letters) will not lead to a change in the results of further analysis.…”
Section: Data For Analysismentioning
confidence: 99%
“…It means the introduction section, educational writing genre (Kawase, 2015) received the most grammatical complexity, and the methodology section was the least one. Though the current study did not focus on reasons for the grammatical complexity growth in 2016's English undergraduate theses, it is obvious that sentence length is a robust measure of sentence structure (Vieira, Picoli, & Mendes, 2018). This means that the growth of the MLS predicts undergraduate's improved writing.…”
Section: Grammatical Complexitymentioning
confidence: 91%
“…An analysis of fractality of sentence-length series in several Western fictional texts revealed that, although most fictional texts show a long-range correlation, the degree of multifractality can vary quite substantially, ranging from monofractal to highly multifractal structure (Drożdż et al, 2016 ). Although sentence length can be measured in various ways, e.g., as the number of characters or words in unlemmatized and lemmatized texts, the different ways yield robust results that have comparable distributions and similar patterns of long-range correlations (Vieira et al, 2018 ). MFDFA has also been applied in empirical studies of reading (Wallot et al, 2014 ).…”
Section: Global Measures Of Variability and Self-similaritymentioning
confidence: 99%